Twice Applications of Laying Hens Manure Produced the Highest Yield of Organic Okra Pods (Abelmoschus esculentus L. Moench.) - Fhonna, Tasya Nurizki; Melati, Maya; Aziz, Sandra Arifin (Department of Agronomy and Horticulture, IPB University, 2023)
The optimal okra cultivation using organic fertilizers remains a subject of limited information. This study aimed to assess the impact of applying 18 t.ha-1 of laying hens' organic fertilizer on the morphological and physiological traits of the